Narrative Policy Analysis: What is Behind The Movement of Capital City of Indonesia - Harriswara Akeda; Muh Aziz Muslim (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The relocation of the Indonesian Capital from Jakarta to Nusantara in North Penajam Paser has generated both support and opposition. The urgency of the idea has been criticized as not taking into account the current conditions, which is still recovering from the pandemic and facing uncertainties in the global economic situation. To understand this situation, this study used narrative policy framework method to analyze the government's narrative in implementing capital relocation policy, as compared to the counter-narrative conveyed by the community. The government believes that relocation is the best solution to resolving the pressing issues of economic disparity and environmental changes on Java Island. They also claim that the new capital would be a showcase of Indonesia's diversity to the world. On the other hand, the community views policy as being unfavorable to their interests, more business-oriented, and politically driven. The government is seen as unresponsive to the community's needs. The results showed that there was a gap between narrative of capital relocation policy conveyed by the government and the community who opposed this policy. In addition, the government's failure to involve the community in the formulation of policy has resulted in conflicting interests and different perspectives during the implementation stage.